Endometrial polyps: Is the prediction of spontaneous regression possible? - Semra Yuksel; Guray Tuna; Hale Goksever Celik; Suleyman Salman (Korean Society of Obstetrics and Gynecology, 2021)
Objective Endometrial polyps have been considered as a hyperplastic growth of endometrial stromal and glandular tissues. Even asymptomatic polyps in premenopausal women are usually removed as soon as they are diagnosed, although it is still unknown how often endometrial polyps disappear spontaneously. The aim of this study was to investigate the regression rate of endometrial polyps and the possible factors related to their spontaneous regression. Methods A total of 197 women with endometrial polyps were treated with operative hysteroscopy between January 2017 and April 2019 at our tertiary center. Of these, 123 patients who preferred conservative follow-up were enrolled in the study. Clinical and pathological data were obtained from electronic medical records. Results Patients with endometrial polyps were followed up for a median period of 62 days (range 30-360 days). Most women with endometrial polyps (84%) were reported to have gynecologic symptoms. Spontaneous polyp regression was observed in 28 (23%) patients who underwent surgery reevaluation. Patient age (<45 years), premenopausal period, and polyp size (<2 cm) were found to be associated with spontaneous endometrial polyp regression (P<0.05). We also observed more polyp regression in women with abnormal uterine bleeding (P=0.05). Second-look hysteroscopy showed that all postmenopausal women had persistent endometrial polyps. Conclusion Patient age (<45 years), premenopausal period, polyp size (<2 cm), and abnormal uterine bleeding may be associated with spontaneous endometrial polyp regression.